Cost drivers associated with autologous stem-cell transplant (ASCT) in patients with relapsed/refractory diffuse large B-cell lymphoma in a Japanese real-world setting: A structural equation model (SEM) analysis 2012–2022 - Saaya Tsutsué; Shinichi Makita; Hiroya Asou; Shingo Wada; Wen Shi Lee; Dilinuer Ainiwaer; Koki Idehara; Sona-Sanae Aoyagi; Seok-Won Kim; Todd Taylor (PLoS ONE, 2025)
Diffuse large B-cell lymphoma (DLBCL) is the most prevalent non-Hodgkin lymphoma, with increasing incidence, in Japan. It is associated with substantial economic burden and relatively poor survival outcomes for relapsed/ refractory (r/r) DLBCL patients. Despite its association with economic burden and the relatively limited number of eligible patients in Japan as reported in previous real-world studies, Japanese clinical guidelines recommend stem-cell transplantation (SCT) for transplant-eligible r/r DLBCL patients. This is the first study to elucidate the total healthcare cost, associated cost drivers and healthcare resource use of SCT among patients with r/r DLBCL in a nationwide setting. The study design included a follow-up period of up to 24 months with subsequent lines of therapies using retrospective nationwide claims data from the Medical Data Vision Co., Ltd. Health Insurance Association from April 2012 to August 2022. Included patients had a confirmed diagnosis of DLBCL, received allogeneic SCT (allo-SCT) or autologous SCT (ASCT) after the first DLBCL diagnosis, and received high-dose chemotherapy during the 6-month look-back period. The results confirmed that no patients had allo-SCT, hence only ASCT was included in the analysis. Structural equation modeling was used to identify potential total healthcare cost drivers by evaluating direct, indirect, and total effects and provide a benchmark reference for future innovative therapies. A total of 108 patients (3.8%) among all DLBCL patients who received SCT met the eligibility criteria and were considered ASCT patients; majority of which were males (n = 63, 58.33%), with a mean [median] (SD) age of 52.04 [55] (9.88) years. A total of 15 patients (13.89%) received subsequent therapies. The most frequent subsequent therapy was GDP-based with or without rituximab (n = 8, 7.41%). The mean [median] (SD) number of follow-up hospitalizations on or after SCT-related hospitalizations was 1.66 [1] (1.36), with a mean [median] (SD) length of hospital stay being 36.88 [34] (12.95) days. The total mean [median] (SD) healthcare cost after adjustment incurred per patient per year during follow-up was $79,052.44 [$42,722.82] ($121,503.65). Number of hospitalizations and Charlson Comorbidity Index scores (+5) were the key drivers of total healthcare costs in patients with r/r DLBCL. Index years 2020–2022 and heart disease as a complication were other statistically significant factors that had positive effects as increase on total healthcare costs.